Measuring and analyzing the efficiency of commercial banks operating in Algeria using the Data Envelope Analysis method -Study of a group of public and private banks during the year 2019- - benaichouche, mohamed; Hamou, abdellah (Journal of Research in Finance and Accounting, 2022)
This study aims to measure and analyze the efficiency of Algerian commercial banks. To achieve this objective, we have applied Data Envelopment Analysis (DEA) method using General charges of exploitation and deposits as inputs, net banking income, credits, and interest and commission margin as outputs. With variable return to scale (VRS) and output-oriented. The results indicate that, there is a difference in efficiency scores and the inefficient banks can performance efficiently with regard to their peers, and foreign banks are more efficient than national ones.